(untitled) (American Journal of Economics and Business Innovation, 2025)
This paper examines the role of Information and Communication Technologies (ICT) in enhancing financial inclusion across 120 countries from 2004 to 2017. Employing a dynamic panel data (Generalized Method of Moments, GMM) methodology, it addresses two primary questions: how communication technology affects financial inclusion and whether the gains differ across developing, emerging, and developed nations. The results indicate a positive and statistically significant impact of communication technology on financial inclusion, with a relatively higher elasticity for mobile phone users in middle-income and high-income countries. Furthermore, the significance of physical bank branches diminishes once communication technology variables are included, suggesting a distinct channel through which ICT fosters financial access. The elasticity of physical bank outlets is higher for middle-income economies than for high-income counterparts, whereas the influence of communication technology is greater among high-income countries. These findings call into question potential diminishing marginal returns from communication technology. Although the model includes less developed countries in the sample, it does not adequately explain their within-group variation.